The Effect of Giving Additional Food to Pregnant Women with Chronic Energy Deficiency at Ribang Community Health Center - Erdi Yani; Sulistiyah Sulistiyah; Retno Dewi Prisusanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Chronic Energy Deficiency (CHD) is a condition resulting from an imbalance in the intake of energy and protein nutrients needed by pregnant women. The impact of CHD during pregnancy can lead to severe complications, including an increased risk of maternal and infant mortality. To address this, the Supplementary Feeding Program (PMT) is often implemented to improve the nutritional intake of pregnant women. The aim of this study was to determine the effect of PMT on pregnant women with SEZ (Chronic Energy Deficiency) at the Ribang Health Center. The sample consisted of 15 respondents. Data collection involved measuring the upper arm circumference (LILA) of pregnant women using a LILA tape and an observation sheet to track PMT participation. The research employed a non-equivalent quasi-experimental design, utilizing a quantitative approach with a one-group pretest-posttest design. Data analysis was conducted using the Wilcoxon statistical test to assess changes in the participants' LILA before and after the intervention. The results showed a notable improvement in the size of the upper arm circumference (LILA) in the respondents after receiving the PMT intervention. Before the intervention, 100% of the respondents had a LILA measurement of less than 23.5 cm, indicating chronic energy deficiency. After the intervention, 40% of respondents still had a LILA measurement of less than 23.5 cm, but 60% of the respondents showed a significant improvement with a LILA greater than 23.5 cm. The statistical analysis revealed a significant difference in LILA measurements before and after the intervention, with a p-value of 0.000. In conclusion, the provision of PMT has a significant positive effect on improving the nutritional status of pregnant women with chronic energy deficiency, as evidenced by the increase in their LILA measurements